Analisis Bibliometrika Pariwisata Halal di Indonesia - Lailan Safina Hasibuan (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
The tourism sector contributes greatly to the economy. Besides that, it also acts in expanding job opportunities and also as a foreign exchange earner. Changes in people's preferences for halal tourism causing high attention to this sector, Thus, sharia hotels have sprung up. To answer this, then the National Sharia Council issues fatwa No 108/DSN-MUI/X/2016 as a guide in running halal tourism. Of the many points that must be adhered to in running a sharia hotel,it turns out that the difficult point to run is halal certification for food and drink and the use of Islamic financial institutions. This research is a literature study, who analyzed the literature on the same theme in the last 5 years, found on Google Scholar by using the Publish or Perish application. The results of the study show that halal tourism actors in Indonesia, have not been able to fully follow the guidelines of the fatwa DSN-MUI due to several factors.